2017
DOI: 10.1007/s00402-017-2659-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous radioscapholunate fusion after septic arthritis of the wrist: a case report

Abstract: Bacterial septic arthritis rarely occurs in the upper extremities. Yet, early diagnosis and treatment is important, as a delay in diagnosis results in pain, impaired hand function, and degenerative joint disease. Radioscapholunate (RSL) arthrodesis is a well-established procedure for treating inflammatory arthritis and osteoarthritis (primary or posttraumatic), primarily to achieve pain relief. The wrist deformity correction offers an alternative option to total wrist arthrodesis. Indications for a RSL arthrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…They were partly used in combination with external fixation. However, secondary dislocation still occurred [9][10][11][12][13][14], that necessitated correction and salvage procedures [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…They were partly used in combination with external fixation. However, secondary dislocation still occurred [9][10][11][12][13][14], that necessitated correction and salvage procedures [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…arthritis. 6 However, this case is very rare and surgical reconstruction is usually required. Deml et al reported total wrist arthrodesis using vascularized iliac bone autograft.…”
Section: Discussionmentioning
confidence: 99%
“…Septic wrist joint arthritis is a relatively rare condition. 6 The incidence of the condition is reportedly 4-10 per 100,000 patients per year. 7 Septic wrist arthritis accounts for 4% of all septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the introduction of palmar angular stable plate systems, a fixation of dorsally displaced DRF became possible from the palmar aspect of the distal radius. Palmar fixation ensures sufficient stability to allow early active wrist mobilization without immobilization/ splinting [13,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%